Importancia de los sustratos biogénicos para el cangrejo de piedra Menippe nodifrons Stimpson, 1859 (Brachyura: Eriphioidea) - Rodrigues-Alves, Douglas Fernandes [UNESP]; Barros-Alves, Samara de Paiva [UNESP]; Fransozo, Vivian [UNESP]; Bertini, Giovana [UNESP]; Cobo, Valter José [UNESP] (My University, 2013)
In order to better understand the ecology of the different growth phases of the stone crab, Menippe nodifrons, and provide information for conservation of the natural stocks, this study describes the utilization of different biogenic substrates by this species in the intertidal zone. Sampling was carried out by hand at Ubatuba, State of São Paulo, Brazil. Crabs were captured among rocks or in association with three different biogenic substrates: Phragmatopoma lapidosa, Sargassum cymosum and Schizoporella unicornis. In the laboratory, the substrates were sorted and scanned for specimens of M. nodifrons, which were separated and measured at their maximum carapace width (CW), and classified as juvenile or adult specimens. Sex ratio and size distribution of crabs were analyzed for each of the substrate types. A total of 686 specimens of M. nodifrons were obtained during the sampling, ranging in size between 2.4 and 82.5 mm CW. Different mean sizes were recorded in the different substrates (P < 0.05). The high prevalence of juveniles in the samples suggests that these microhabitats are fundamental for the juvenile development of M. nodifrons, as they provide refuge, protection and probably food for juveniles.
Importance of biogenic substrates for the stone crab Menippe nodifrons Stimpson, 1859 (Brachyura: Eriphioidea)
Keywords: Intertidal; Life cycle; Menippe nodifrons; Recruitment; Spatial dynamic; Substrate